1997
DOI: 10.1002/(sici)1097-0010(199711)75:3<378::aid-jsfa887>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Aglycone and glycoside specificity of apple skin flavonoid glycosyltransferase

Abstract: O‐Glycosyltransferase(s) extracted from apple (Malus pumila Mill) fruit skin showed activity towards a range of flavonols and anthocyanins. However, no glycosylating activity was shown towards a dihyroflavonol (dihydroquercetin), a flavanone (eriodictyol) or a flavone (luteolin). The enzyme preparation glycosylated those flavonoids normally present in apple skins (quercetin and cyanidin) and in addition several other related compounds (delphinidin, fisetin, isorhamnetin, kaempferol, myricetin and pelargonidin)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The other point at which substrate competition may occur is glycosylation of quercetin, which provides stability to flavonol compounds. Lister et al (1997) showed the enzyme MdUFGT can catalyse the glycosylation of both cyanidin and quercetin, but had twice the relative activity with cyanidin than with quercetin as substrate. Therefore, substrate competition in vivo could favour the anthocyanin pathway.…”
Section: Discussionmentioning
confidence: 93%
“…The other point at which substrate competition may occur is glycosylation of quercetin, which provides stability to flavonol compounds. Lister et al (1997) showed the enzyme MdUFGT can catalyse the glycosylation of both cyanidin and quercetin, but had twice the relative activity with cyanidin than with quercetin as substrate. Therefore, substrate competition in vivo could favour the anthocyanin pathway.…”
Section: Discussionmentioning
confidence: 93%
“…The different gene expression and enzyme activity responses might be related to the different cultivar properties, as ‘Golden Delicious’ is a non-red cultivar and ‘Fuji’ is a red cultivar. UFGT catalyzes the glycosylation of both cyanidin and quercetin in apple peel [27,40], while DFR is only involved in the synthesis of cyanidin [30,31,32]. Therefore, under relatively high sunlight conditions, the lower concentrations of quercetin-3-glycoside in DPI-treated ‘Fuji’ peels suggest that DPI may inhibit the synthesis of anthocyanin mainly by affecting the activity of UFGT (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…As UFGT catalyzes the transfer of glycosyl moieties from nucleotide sugar donors to the hydroxyl group of anthocyanidins and other flavonoid acceptors such as quercetin or isorhamnetin (Ju et al , Lister et al ), it is not surprising that the peel of red ‘Anjou’ also had higher concentrations of quercetin‐3‐glycoside and isorhamnetin‐3‐glycoside (Fig. ).…”
Section: Discussionmentioning
confidence: 99%